A Family of Hybrid Mappings and Their Fixed Point in Convex Spaces Under Diametral δ Distances - Khan, Ladlay (Sarajevo Journal of Mathematics, 2025)
We prove some results on coincidence and common fixed points for compatible as well as pointwise $R$-weakly commuting mappings satisfying a generalized contraction condition on a complete metrically convex metric space that generalize relevant results due to Ciri\'c and Ume \cite{CirićUme}, Khan \cite{Khan13, Khan14}, Rhoades \cite{Rhoades19} and others.